DURASI PENYINARAN MATAHARI DAN DIURNAL TEMPERATURE RANGE SERTA KAITANNYA DENGAN PERUBAHAN IKLIM DI PONTIANAK, INDONESIA - Nelvi, Afni; Nata, Refky Adi (Jurnal Meteorologi dan Geofisika, 2023)
Sunshine Duration (SD) has an important role in climate change or the weather on the earth. Climate change can be indicated by changing SD values ​​(dimming/brightening) in recent decades. SD and diurnal temperature range (DTR) analysis needs to be done to find out how significant the impact of climate change. The daily dataset from 1981-2019 of SD, DTR, Tmean, Tmax, Tmin, and rainfall in Pontianak, West Kalimantan, is analyzed with Continuous Wavelet Transform (CWT) and wavelet coherence (WTC). Results of CWT using the Morlet wavelet SD have a dominant period of 8-16 months. DTR has a dominant period of 8-16 months and 32-64 months. The increase in SD indicates that Pontianak is in a brightening period caused by changes in the characteristics of clouds and aerosols. It causes an increase in the amount of solar energy reaching the earth's surface. Climate change has been detected by the decrease in DTR. A negative correlation was found between DTR and SD (r = -0.80). DTR is a very good indicator of climate change because of its sensitivity to radiative energy balance. Changes in SD have a significant impact on Tmean, Tmax, and Tmin. The increase of Tmin, faster than Tmax, causes a decrease in DTR. Tmin is predicted to be higher. Tmean and Tmax have dominant periods of 8-16 months, while Tmin has dominant periods of 12-20 months and 32-64 months. The increase in temperature detected during this period is associated with peatland forest fires in Kalimantan. This condition occurs due to the effect of the brightening period and increasing concentrations of greenhouse gases in the atmosphere. Rainfall is detected in the period of 4-8 months and 8-16 months. The drought associated with the El Nino event resulted in a large amount of rainfall deviation from normal.